Mosquito Defensins Enhance Japanese Encephalitis Virus Infection by Facilitating Virus Adsorption and Entry within the Mosquito - Liu, Ke (J Virol, 2020)
Japanese encephalitis virus (JEV) is a viral zoonosis that can cause viral encephalitis, death, and disability. Although the Culex mosquito is the primary vector of JEV, little is known about JEV transmission by this kind of mosquito. Here, we found that mosquito defensin facilitated the adsorption of JEV on target cells via the defensin/lipoprotein receptor-related protein 2 (LRP2) axis. Mosquito defensin bound the ED III domain of the viral envelope (E) protein and directly mediated efficient virus adsorption on the target cell surface; the receptor LRP2, which is expressed on the cell surface, affected defensin-dependent adsorption. As a result, mosquito defensin enhanced JEV infection in the salivary gland, increasing the possibility of viral transmission by mosquitoes. These findings demonstrate the novel role of mosquito defensin in JEV infection and the mechanisms through which the virus exploits mosquito defensin for infection and transmission. IMPORTANCE In this study, we observed the complex roles of mosquito defensin in JEV infection; mosquito defensin exhibited a weak antiviral effect but strongly enhanced binding. In the latter, defensin directly binds the ED III domain of the viral E protein and promotes the adsorption of JEV to target cells by interacting with lipoprotein receptor-related protein 2 (LRP2), thus accelerating virus entry. Together, our results indicate that mosquito defensin plays an important role in facilitating JEV infection and potential transmission.